2023
DOI: 10.3390/ijerph20043008
|View full text |Cite
|
Sign up to set email alerts
|

Better Gingival Status in Patients with Comorbidity of Type 1 Diabetes and Thyroiditis in Comparison with Patients with Type 1 Diabetes and No Thyroid Disease—A Preliminary Study

Abstract: Periodontal disease has been postulated as one of the chronic complications of diabetes. The prevalence of autoimmune thyroiditis in type 1 diabetes (T1D) is higher. The aim of the study was to determine the association between the presence of thyroiditis and gingival status in adults with T1D. A total of 264 patients, 119 men aged 18–45, diagnosed with T1D were included. For further analysis, the study group was divided into two subgroups, with or without autoimmune thyroiditis. Gingival status was assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Lower caries prevalence corresponds with the lower plaque scores, which could mean that DM children have better oral health routines than healthy children [ 37 ]. We have found no significant difference in PI between children with and without DM, that is in line with other studies [ 67 ]. Dental plaque is the strongest risk factor of developing caries, and the fact that PI is similar in the two population elevates the evidence of the impact of DM on caries risk [ 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…Lower caries prevalence corresponds with the lower plaque scores, which could mean that DM children have better oral health routines than healthy children [ 37 ]. We have found no significant difference in PI between children with and without DM, that is in line with other studies [ 67 ]. Dental plaque is the strongest risk factor of developing caries, and the fact that PI is similar in the two population elevates the evidence of the impact of DM on caries risk [ 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…Human clinical studies have indicated a deteriorated periodontal status among patients with thyroid disease [5,17]. There are several possible explanations for the association between periodontitis and AIT.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with children in the control group, children affected by thyroid disorders exhibited a greater prevalence of dental caries and periodontal disease [16]. In addition, a preliminary study suggested that individuals experiencing comorbidity of type 1 diabetes and thyroiditis exhibit improved gingival health compared to those with only type 1 diabetes and no thyroid disease [17].Biological plausibility supports a potential association between Hashimoto's thyroiditis and periodontal disease. However, insu cient studies currently exist to de nitively establish a causal link between these two pathologies [18].…”
Section: Introductionmentioning
confidence: 99%